Cost-efficiency of mastitis control strategies on smallholder dairy farms - A. Fadillah; B.H.P. van den Borne; Y.H. Schukken; O.N. Poetri; H. Hogeveen (Journal of Dairy Science, 2025)
ABSTRACT: Mastitis poses significant challenges to the global dairy industry, including smallholder farms, which contribute substantially to global milk production. In Indonesia, where smallholder farming is vital to the dairy sector, mastitis represents a substantial obstacle to sustainable milk production and farm profitability. The objectives of this study were to estimate the costs associated with mastitis on Indonesian smallholder dairy farms and evaluate the cost-efficiency of various mastitis control strategies. A stochastic Monte Carlo bio-economic simulation model was employed to mimic mastitis dynamics and to estimate the economic effect on a typical Indonesian dairy farm of 4 cows. Input parameter values were gathered from various sources including literature, fieldwork data collection, local research reports, and expert insights obtained from staff of a local cooperative, veterinarians, local university experts, and authors' expertise. Somatic cell count values were added to the model to monitor udder health and milk quality per time period of 2 wk. Blanket dry cow therapy was also included to refine mastitis dynamics. All simulation outcomes were aggregated per year and per farm. Results indicated that clinical and subclinical mastitis incurred costs of €101.98 and €73.22/farm per year, respectively. Clinical mastitis costs were primarily driven by culling (45%) and discarded milk (27%), whereas subclinical mastitis costs were shared between production loss (52%) and blanket dry cow therapy (48%). Five mastitis control strategies were evaluated, including postmilking teat disinfection, a higher manure removal frequency, washing udders with soap, udder health monitoring using the California Mastitis Test (CMT), and antibiotic treatment for subclinical mastitis. Among these, postmilking teat disinfection emerged as the only strategy with a positive net economic benefit, significantly reducing mastitis incidence and associated economic losses. This study further suggests that the cost-efficiency of udder health monitoring using the CMT and antibiotic treatment for subclinical mastitis depends on substantially reducing mastitis incidence. This finding highlights the need for farmers to combine with other cost-efficient control strategies, rather than relying solely on CMT and treatment strategy. Farmers, therefore, need to adopt strategies to lower the incidence rates of clinical and subclinical mastitis, thereby offsetting the costs when applying these strategies. In conclusion, the study emphasizes the economic burden of mastitis on smallholder dairy farms and the critical need for efficient control strategies to support improving the profitability and sustainability of smallholder dairy farms.